Characterization of differential throughfall drop size distributions beneath European beech and Norway spruce. Issue 26 (5th September 2019) - Lüpke, Marvin; Leuchner, Michael; Levia, Delphis; Nanko, Kazuki; Iida, Shin'ichi; Menzel, Annette
Abstract: Forest canopies present irregular surfaces that alter both the quantity and spatiotemporal variability of precipitation inputs. The drop size distribution (DSD) of rainfall varies with rainfall event characteristics and is altered substantially by the forest stand properties. Yet, the influence of two major European tree species, European beech ( Fagus sylvatica L.) and Norway spruce ( Picea abies (L.) H. Karst), on throughfall DSD is largely unknown. In order to assess the impact of these two species with differing canopy structures on throughfall DSD, two optical disdrometers, one above and one below the canopy of each European beech and Norway spruce, measured DSD of both incident rainfall and throughfall over 2 months at a 10‐s resolution. Fractions of different throughfall categories were analysed for single‐precipitation events of different intensities. While penetrating the canopies, clear shifts in drop size and temporal distributions of incoming rainfall were observed. Beech and spruce, however, had different DSD, behaved differently in their effect on diameter volume percentiles as well as width of drop spectrum. The maximum drop sizes under beech were higher than under spruce. The mean ± standard deviation of the median volume drops size (D50) over all rain events was 2.7 ± 0.28 mm for beech and 0.80 ± 0.04 mm for spruce, respectively. In general, there was a high‐DSD variability within events indicating varying amounts of the different throughfall fractions. These findings help to better understand the effects of different tree species on rainfall partitioning processes and small‐scale variations in subcanopy rainfall inputs, thereby demonstrating the need for further research in high‐resolution spatial and temporal properties of rainfall and throughfall. Abstract : Scheme of throughfall fractions separation by subtraction of rainfall (tower) and throughfall (floor) spectra and a canopy. Throughfall is split into three parts: TFs : splash, TFd : drip, and TFmix : mixed fraction TFmix, containing free TF and not distinguishable TF from TFd or TFs .